Efficacy of trinapanchamoolkwath in the management of urinary tract infection during pregnancy (Mutrakruccha in Garbhini) - A case study - Preeti Chouhan; Ayush Kumar Garg (Wolters Kluwer Medknow Publications, 2022)
Introduction: Urinary tract infection during pregnancy and postpartum is a common obstetric complication. The term Mutrakruchhacomes under the disorders of MutravahaSrotas, and mainly deals with shool (pain) and krucchrata (dysuria). This article discusses a female patient with a history of 6 months 24 days of pregnancy seen in the OPD of Prasuti Tantra, Sir SundarlalHospital, IMS, BHU. Main Clinical Finding: Her chief complaints were painful, difficult urination with burning along with pain in the suprapubic region for 8 days. Diagnosis: In this case, the patient has an urge to micturate, but she passes urine with pain. The painful voiding of urine is diagnosed as Mutrakruchha. Interventions: After appropriate analysis based on ayurvedic and modern parameters, the patient was treated with Trinapanchmulakwath. Outcome: Before treatment, her scoring of subjective parameters was 13 and after treatment, her score decreased to 2. Thus, the treatment module showed significant relief in the symptoms by 84.62%. Laboratory investigation showed marked improvement as pus cells were reduced to 0-1/high power field (HPF) from 10 to 12/HPF and epithelial cells were reduced to 1-2/HPF from 9 to 10/HPF. Conclusions: All the symptoms and investigations showed highly significant results, hence it can be concluded that this medicine is very effective in patients of garbhinimutrakruchha.